UNDERSTANDING HOW HARIAN JOGJA NEWSPAPERS FACE THE CHALLENGES OF MEDIA DIGITALIZATION - Putra, Eagan Murtadho Dita; Adiyanto, Wiwid; Asrita, Stara (Journal of Digital Media Communication, 2024)
The print media industry is experiencing a decline in circulation. One of the causes is advances in communication technology or digitization. The aim of this research is to describe how Harian Jogja faces the challenges of media digitization. This research uses the media Ecology theory initiated by McLuhan to help broadly describe the phenomena that occur. The method used refers to phenomenology which is used as an analytical tool. The results of this research show that Harian Jogja is trying to create a new alternative to enable their agency or company to continue to survive in any conditions and situations. The Harian Jogja print media tries to shift its marketing strategy to non-print form. The Harian Jogja creates a strategy in presenting news, namely regional news and also an ABC reporting strategy, namely accurate, actual, brief, balanced, clear and complete.